Factors Affecting The Use of Management Accounting Practices in Small and Medium Enterprises: Evidence from Indonesia - Prihastiwi, Diah Agustina; Sholihin, Mahfud (Jurnal Dinamika Akuntansi, 2018)
Small and medium sized enterprises (SMEs) contribute to the development of both developed and developing countries economy. Nevertheless, the focus of the studies in management accounting field is still in the developed countries. Studies on the adoption of management accounting practices (MAPs) in developing countries are still too little. This study explores the level of adoption of MAPs in SMEs sector in one of the developing countries in Indonesia. This study also examines factors which may affect the extent of use of MAPs in SMEs. Logistic regression is applied to analyze the data and to test the hypotheses. It is observed that qualification of internal accounting staffs, participation of owner/manager, and size of the firm significantly affect the use of MAPs in SMEs. The paper serves as a stepping stone to the research in the fields of management accounting and organizational design in Indonesian SMEs.